EFECTIVIDAD DE LOS DESINFECTANTES ALTERNATIVOS: ÁCIDO PERACÉTICO Y ORTOFTALALDEHÍDO EN COMPARACIÓN CON EL GLUTARALDEHÍDO PARA LOGRAR UNA DESINFECCIÓN ÓPTIMA Y SIN DAÑOS, EN LOS ENDOSCOPIOS FLEXIBLES - Alvarez Avalos, Hiozime (2018)
Systematic review of 06 research articles and international studies , the most relevant ones have been included according to the level of evidence has been restricted to articles with full text, in the 06 articles reviewed systematically, 50% are systematic review, 33% are controlled clinical trials and 16% are experimental studies, has subjected to a critical reading, using the scale scale. Results: Of the 06 articles reviewed, 02 of them show that the disinfectants studied are effective in the inactivation of vegetative microorganisms, under the established conditions of use, 02 articles show that the previous conditions are important to guarantee an adequate disinfection, in 03 articles it is evident that the use of orthophalaldehyde as well as glutaraldehyde and peracetic acid have been cited in relation to its toxicity, so as an alternative it would not be safe. No studies have been identified that report damage to endoscopes caused by disinfectants. Conclusions: of the 06 articles reviewed it is evident that the disinfectants peracetic acid and orthophthaladehyde are effective in the inactivation of microorganisms, there must be previous conditions to guarantee an adequate disinfection, disinfectants have been cited for their toxicity, no studies have been identified that report damages in the endoscopes.